"Lutembacher's Syndrome" - A Case Report (Faridpur Medical College Journal, 2011)
Lutembacher's Syndrome is a rare heart disease comprises ASD (congenital) secundum with Mitral stenosis (Rheumatic origin). The patient Md. Mosharraf Hossain, 72 years old man, non diabetic, non hypertensive, smoker admitted in FMCH on 10.10.2010 with the complaints of respiratory distress and chest pain for 10 days. He had a previous history of Rheumatic fever in early childhood. There was history of recurrent attack of Rheumatic fever. Subsequently he developed MS from Rheumatic carditis. ASD was congenital in origin. If diagnosis could be done earlier, surgical closure of ASD with replacement of mitral valve bears a good prognostic value. Our patient is in elderly age and already developed pulmonary hypertension, operative procedure is not suitable. So the patient should be kept in conservative treatment. Key words: Lutembacher's syndrome; Atrial Septal Defect; Mitral stenosis; Septum primium; Septum secundum.   DOI: 10.3329/fmcj.v6i1.7414 Faridpur Med. Coll. J. 2011;6(1): 59-60